2019
DOI: 10.1101/741652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphoproteomics reveals that the hVPS34 regulated SGK3 kinase specifically phosphorylates endosomal proteins including Syntaxin-7, Syntaxin-12, RFIP4 and WDR44

Abstract: The serum-and glucocorticoid-regulated kinase (SGK) isoforms contribute resistance to cancer therapies targeting the PI3K pathway. SGKs are homologous to Akt and these kinases display overlapping specificity and phosphorylate several substrates at the same residues, such as TSC2 to promote tumor growth by switching on the mTORC1 pathway. The SGK3 isoform is upregulated in breast cancer cells treated with PI3K or Akt inhibitors and recruited and activated at endosomes, through its phox homology domain binding t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…44 Furthermore, it would be interesting to explore the effects that SGK3 PROTAC degraders have on selective SGK3 substrates such as STX7 and STX12 that have recently been described that are not phosphorylated by Akt isoforms. 46 The finding that growth of SGK3 dependent cancer cell lines is suppressed more efficiently by SGK3-PROTAC1 than achieved by the 14H non-PROTAC inhibitor provides a further example of the benefit of the PROTAC approach in targeting protein kinase signaling pathways with greater efficacy and selectivity than can be achieved with conventional inhibitors. Other examples include the recent finding that a BCR-ABL degrader displays more sustained inhibition of chronic myelogenous leukemia cell growth than can be achieved by a conventional ABL kinase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Furthermore, it would be interesting to explore the effects that SGK3 PROTAC degraders have on selective SGK3 substrates such as STX7 and STX12 that have recently been described that are not phosphorylated by Akt isoforms. 46 The finding that growth of SGK3 dependent cancer cell lines is suppressed more efficiently by SGK3-PROTAC1 than achieved by the 14H non-PROTAC inhibitor provides a further example of the benefit of the PROTAC approach in targeting protein kinase signaling pathways with greater efficacy and selectivity than can be achieved with conventional inhibitors. Other examples include the recent finding that a BCR-ABL degrader displays more sustained inhibition of chronic myelogenous leukemia cell growth than can be achieved by a conventional ABL kinase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of the stability of the ternary complexes of SGK3 PROTAC compounds with SGK/S6K isoforms and the VHL E3 ligase would be important to better understand the potency and specificity of these PROTACs . Furthermore, it would be interesting to explore the effects that SGK3 PROTAC degraders have on selective SGK3 substrates such as STX7 and STX12 that have recently been described that are not phosphorylated by Akt isoforms . The finding that growth of SGK3 dependent cancer cell lines is suppressed more efficiently by SGK3-PROTAC1 than achieved by the 14H non-PROTAC inhibitor provides a further example of the benefit of the PROTAC approach in targeting protein kinase signaling pathways with greater efficacy and selectivity than can be achieved with conventional inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the similarity in their kinase domains, it is clear that their activity profiles would overlap in such a model, since the PI(3,4)P2 that drives PDK1 and Akt activation must be present in membranes that support PI3P-and PDK1-mediated Sgk3 activation. Indeed, a recent phosphoproteomic study identified several Sgk3specific substrates localized on endosomes (59). The reported role of Sgk3 in driving human cancers in the absence of Akt hyperactivation is then also reconcilable with this model and reinforces the potential value of Sgk3 as a therapeutic target either as a monotherapy or in combination with Akt inhibitors.…”
Section: Discussionmentioning
confidence: 63%